Xerostomia and associated factors among adults with HIV on HAART attending voluntary counseling and testing (VCT) clinics in Dar Es Salaam - Lilian Ephrem Mkonyi; Luciana Albert Mmary (BMC Oral Health)
Abstract Background Adequate saliva quantity and quality are necessary for proper oral function and protection. Xerostomia, or dry mouth, is a common complaint among people living with HIV (PLHIV) which increases their risk of acquiring oral diseases. This study aimed to assess the magnitude of xerostomia and the associated factors in this group of patients. Methods A descriptive cross-sectional hospital-based study was conducted among 420 PLHIV on highly active antiretroviral therapy (HAART) aged 18 years and above. Informed consent was obtained from the participants during data collection. The xerostomia was assessed using a questionnaire. Pearson’s χ2 test was used to correlate independent (sociodemographic factors, oral health-related, and HIV-related factors) and dependent variables (xerostomia). Univariate and adjusted multinomial logistic regression were used to determine the odds ratio (OR) of xerostomia. Results Xerostomia was observed in 36.3% of the respondents. The chi-square test showed a significantly higher proportion of xerostomia among the unemployed (p = 0.014), those who were HIV diagnosed up to five years (p = 0.014), and those having CD4+ counts ≥ 500 cells/ mm³ (p = 0.03). In multivariate analysis, higher odds of having xerostomia were found among participants with higher viral load (OR = 2.6; CI = 1.07–6.3), whereas lower odds were found among self-employed participants (OR = 0.48; CI = 0.28–0.82) and employed participants (OR = 0.52; CI = 0.27–0.98). Conclusion The prevalence of xerostomia is moderately high among PLHIV. Higher viral load and unemployment were the associated factors with xerostomia. Low CD4+ counts, duration of HAART use, and HAART regime were not associated with xerostomia.